Revised Manuscript with Corrections: Polyurethane-Based Conductive Composites: From Synthesis to Applications - Choi, Soon-Mo; Shin, Eun-Joo; Zo, Sun-Mi; Rao, Kummara-Madhusudana; Seok, Yong-Joo; Won, So-Yeon; Han, Sung-Soo (International journal of molecular sciences, 2022)
The purpose of this review article is to outline the extended applications of polyurethane (PU)-based nanocomposites incorporated with conductive polymeric particles as well as to condense an outline on the chemistry and fabrication of polyurethanes (PUs). Additionally, we discuss related research trends of PU-based conducting materials for EMI shielding, sensors, coating, films, and foams, in particular those from the past 10 years. PU is generally an electrical insulator and behaves as a dielectric material. The electrical conductivity of PU is imparted by the addition of metal nanoparticles, and increases with the enhancing aspect ratio and ordering in structure, as happens in the case of conducting polymer fibrils or reduced graphene oxide (rGO). Nanocomposites with good electrical conductivity exhibit noticeable changes based on the remarkable electric properties of nanomaterials such as graphene, RGO, and multi-walled carbon nanotubes (MWCNTs). Recently, conducting polymers, including PANI, PPY, PTh, and their derivatives, have been popularly engaged as incorporated fillers into PU substrates. This review also discusses additional challenges and future-oriented perspectives combined with here-and-now practicableness.